CHEMICAL COMPOSITION AND ANTIMICROBIAL ACTIVITY OF DITERPENE AND ESSENTIAL OILS OF Hedychium roxburghii BL. RHIZOME - Hartati, Rika; Suganda, Asep Gana; Fidrianny, Irda (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: The objective of the present study were to isolate and determine diterpene compound and essential oils from H. roxburghii Bl. rhizome, and investigated those antimicrobial activity. Methods: The essential oils was obtained by steam distillation method, the residual was then extracted by reflux with ethanol. The content of essential oils was analyzed by GC/MS method.Â Ethanolic residual-distillation extract was concentrated then used to isolate compound 1 by vacuum liquid chromatography and centrifugal chromatography. It was characterized by infrared spectrophotometry, 1H-NMR, 13C-NMR, HSQC-NMR, HMBC-NMR and carbon coupling NMR. The antimicrobial activity of essential oils, ethanolic residual-distillation extract and compound 1 were carried out by microdilution method. Results: The oils exhibited antimicrobial activity against Bacillus subtilis ATCC 6633 (MIC 1,750 Î¼g/ml), Staphylococcus aureus ATCC 6538 (MIC 1,750 Î¼g/ml), Escherichia coli ATCC 8939 (MIC 3,500 Î¼g/ml), Pseudomonas aeruginosa ATCC 9027 (> 3,500 Î¼g/ml) and Candida albicans ATCC 10231 (MIC 875 Î¼g/ml). A phytochemical study of the rhizome essential oils of H. roxburghii Bl. were performed by GC/MS and the result showed that fenchyl acetate (45.85%) was the main component of the oils. Compound 1 was identified as diterpene compound, coronarin E. Coronarin E have not exhibited MIC at 512 Î¼g/ml, however it showed inhibition profile against all of tested microbes. Conclusion: The essential oils and ethanolic residual-distillation extract of H. roxburghii Bl. rhizome exhibited weak antimicrobial profile. Compound 1 was identified as diterpene compound, (coronarin E), it was exhibited weak antimicrobial activity, but showed inhibition profile against all of tested microbes. Â Keywords: Hedychium roxburghii, Zingiberaceae, antimicrobial, essential oils, coronarin E